Analysis and design of axially loaded pile response to excavation-induced soil movement - Wong, Soon Yee (2019)
There is a challenge for deep excavation works in existing build areas to cater for urban growth and sprawl, with the alternative to build upwards. These soil excavations with limited construction space could affect the performance of adjacent piles, and foundation failures have been reported since then. In modelling soil-pile interaction, it is important to accurately predict or quantify the pile responses of such incidents to ensure the stability of structures. The reliability of existing methods that are two-staged and those that tend to neglect the nonlinear characteristics of soil-pile interaction, is still being discussed. Currently, researchers are increasingly in favour of three-dimensional (3D) finite element modelling (FEM) during the design process to better understand ground mechanisms and soil-structure interactions.